2022
DOI: 10.1186/s12943-022-01649-y
|View full text |Cite
|
Sign up to set email alerts
|

Ligands stimulating antitumour immunity as the next G-quadruplex challenge

Abstract: G-quadruplex (G4) binders have been investigated to discover new anticancer drugs worldwide in past decades. As these ligands are generally not highly cytotoxic, the discovery rational was mainly based on increasing the cell-killing potency. Nevertheless, no G4 binder has been shown yet to be effective in cancer patients. Here, G4 binder activity at low dosages will be discussed as a critical feature to discover ligands with therapeutic effects in cancer patients. Specific effects of G4 binders al low doses ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 143 publications
0
20
0
Order By: Relevance
“… 29 , 30 Even though the definition of the mechanism likely needs future investigations, however, the activation of other cytoplasmic signaling pathways may affect the recognition of micronuclei and activation of the STING pathway. 5 , 29 , 30 Autophagic processes are known to be activated by G4 binders 3 , 31 , 32 and can regulate the STING pathway through recycling micronuclei and DNA by forming autophagosomes. 33 , 34 Interestingly, autophagic gene pathways were not activated at high levels in MCF-7 cells treated with PDS , which can activate at very high levels the IFN-B gene and other genes stimulated by IFN-B.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 29 , 30 Even though the definition of the mechanism likely needs future investigations, however, the activation of other cytoplasmic signaling pathways may affect the recognition of micronuclei and activation of the STING pathway. 5 , 29 , 30 Autophagic processes are known to be activated by G4 binders 3 , 31 , 32 and can regulate the STING pathway through recycling micronuclei and DNA by forming autophagosomes. 33 , 34 Interestingly, autophagic gene pathways were not activated at high levels in MCF-7 cells treated with PDS , which can activate at very high levels the IFN-B gene and other genes stimulated by IFN-B.…”
Section: Discussionmentioning
confidence: 99%
“… 1 4 Despite the large number of specific ligands developed, none has however shown efficacy in cancer patients and very few have reached early phases of clinical trials. 5 , 6 In line with the standard drug discovery rationale, several laboratories have previously searched for G4 binders with a high cell-killing potency. 1 5 Interestingly, we have recently demonstrated that the G4 binders pyridostatin ( PDS ) and PhenDC3 can effectively elicit an innate immune gene response [activation of interferon β (IFN-B) gene and IFN-B-dependent pathways] in human cancer cells, mediated by micronuclei accumulation at non-cytotoxic concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations